Effects Parental Verbal and Non-Verbal Abuse on the Teenager’s Self-Disclosure in Pangkalan Mahsyur Villange, Medan Johor Subdistrict Medan Munipality - Hazrina Syahirah Putri; Mazdalifah Mazdalifah; Dewi Kurniawati (Yayasan Adra Karima Hubbi, 2024)
Background. The first education that children encounter is from their parents. However, not all parents understand the importance of education. The reality, family becomes a place of ineffective communication. Office of Women’s Empowerment Women’s Empowerment and Child Protection Office of Medan Johor Sub-district, Medan City, in 2022 states that verbal communication violence is a problem today. Based on data from the Central Bureau of Statistics of Medan City in 2023, Kelurahan Pangkalan Mahsyur is the urban village with the largest population in the Medan Johor sub-district. Purpose. The purpose of this research is to determine and analyze the effect of verbal and nonverbal communication violence on adolescent self-disclosure. Method. This research method uses a quantitative approach with descriptive and correlation methods. The data collection technique is probability sampling with 370 samples in Pangkalan Mahsyur Village. Data shows the variable of verbal communication violence, the dimension of yelling obtained a value of 38.9%. Nonverbal communication violence variable, facial expression dimension obtained a value of 41.8%. Results. The results of The results show that the hypothesis H0 is rejected and H1 is accepted that there is an influence of verbal and nonverbal communication violence on self-disclosure. influence of verbal and nonverbal communication violence on the self-disclosure of adolescents in adolescents in Pangkalan Mahsyur Village, Medan Johor Subdistrict, Medan City, with an influence of 5.1%. with a magnitude of influence of 5.1%. Conclusion. The conclusion in this study found that verbal communication violence has a greater influence than nonverbal communication violence. This means, there is a low categorised relationship between the relationship of verbal communication violence, nonverbal communication violence with adolescent self-disclosure in adolescents.